Toward A Method Of Middle-Range Theorizing - Bourgeois, L. J. (Academy of Management Review, 1979)
This article presents an attempt at constructing a catalog of tools for middle-range theory in organizational research. The author notes that middle-range theory can be classified into the sub-categories of substantive and formal theory. Substantive theories tend to center on their databases while formal theory is generated through the comparative analysis of various substantive theories. The theoretical work consists of partitioning of the field under investigation, method of theory construction, review of literature, construction of theory, extension of theory, metaphysical elaboration and conclusion. Inductive inferences start with observations of a set of phenomena, after which one arrives at general conclusions.